2011
DOI: 10.1007/s00436-011-2320-9
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the chelerythrine, a quaternary benzo[c]phenanthridine alkaloid from Chelidonium majus L. on Dactylogyrus intermedius

Abstract: Dactylogyrus intermedius is a significant monogenean parasite on the gills of cyprinid fishes and can cause severe economic losses in aquaculture and ornamental fish breeding. In the present study, bioactivity-guide fractionation was employed to identify active compound from Chelidonium majus L. against D. intermedius. In vivo anthelmintic activity of petroleum ether, ethyl acetate, chloroform, and n-butanol extracts of C. majus were tested. Among them, only the n-butanol extract exhibited promising anthelmint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Solanaceae are known for possessing a diverse range of alkaloids, like solasodine, solakhasanin, solamargine and khasinin (Weissenberg 2001). And, many previous studies have assigned the antiparasitic effects of medicinal plants to these alkaloids (Athanasiadou and Kyriazakis 2004;Li et al 2011). With an estimated 1,400 species, Solanum is the largest genus in Solanaceae and one of the medicinally important groups of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Solanaceae are known for possessing a diverse range of alkaloids, like solasodine, solakhasanin, solamargine and khasinin (Weissenberg 2001). And, many previous studies have assigned the antiparasitic effects of medicinal plants to these alkaloids (Athanasiadou and Kyriazakis 2004;Li et al 2011). With an estimated 1,400 species, Solanum is the largest genus in Solanaceae and one of the medicinally important groups of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the tested extracts from C. majus whole plant, the ethanolic extract was found to be most effective when tested against the fish parasite D. intermedius (Li et al 2011), indicating that the active constituents were mainly contained in this preparation. Therefore, bioassay-guided purification was conducted in the present study with this extract, yielding an active compound.…”
Section: Resultsmentioning
confidence: 94%
“…Previous chemical and pharmacological studies found that it mainly contained various isoquinoline alkaloids which exhibited antimicrobial, anticancer, anti-inflammatory, adrenolytic, sympatholytic, and anti-acetylcholinesterase activities (Jiangsu New Medical College 1977;Niu and He 1994;Táborská et al 1995;Colombo and Bosisio 1996;Cho et al 2006). Our previous study exhibited that ethanol extract from C. majus showed significant effect with an EC 50 (median effective concentration) value of 71.5 mg L −1 against D. intermedius (Li et al 2011); it prompted us to conduct a further investigation on this plant, aiming to isolate and purify the active compounds responsible for its anthelmintic properties.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The alkaloids cause limpness and tone reduction of smooth muscle in rabbits. The alkaloids are also noted to stimulate the heart and lungs of frogs, cats and dogs, raising the blood pressure and widening the arteries [20][21][22].…”
Section: Introductionmentioning
confidence: 99%